Indeks kemiskinan pelbagai dimensi sebagai alternatif pengukuran kemiskinan: Kajian kes di Daerah Baling, Kedah - Che Mat, Siti Hadijah; Abdul Hakim, Roslan; Jumali, Siti Norliza (Universiti Kebangsaan Malaysia, 2012)
Currently, the measurement of poverty uses one-dimensional approach that is, whether income or expenditure.By using only one variable (dimension) to classify a household is poor or not, it unable to give precise guidance on poverty.Therefore, in this article, we used Multidimensional Poverty Index (MPI).There are 14 indicators in four dimensions studied.The dimensions are education, health, living standards and wealth.This article used multidimensional poverty index as an alternative for measuring poverty in seven location in district of Baling, Kedah.The results shows, 87.37 percent of households are deprived in obtaining nutrition and about 70.20 percent of households are deprived in the dimension of land ownership.The advantage of this measurement beside knowing the dimensions deprived by a society, this method also can be separated either in rural areas, gender, religion and race.Therefore, it is recommended to achieve more effective poverty eradication, a more appropriate and in conformity with the conditions of poverty must be done so that the solution can be made as needed.